Production of Whey Protein-Based Aggregates Under Ohmic Heating - Pereira, Ricardo N; Rodrigues, Rui M; Ramos, Óscar L; Xavier Malcata, F; Teixeira, José António; Vicente, António A (Food and bioprocess technology, 2016)
Formation of whey protein isolate protein aggregates under the influence of moderate electric fields upon ohmic heating (OH) has been monitored through evaluation of molecular protein unfolding, loss of its solubility, and aggregation. To shed more light on the microstructure of the protein aggregates produced by OH, samples were assayed by transmission electron microscopy (TEM). Results show that during early steps of an OH thermal treatment, aggregation of whey proteins can be reduced with a concomitant reduction of the heating charge—by reducing the come-up time (CUT) needed to reach a target temperature—and increase of the electric field applied (from 6 to 12 V cm⁻¹). Exposure of reactive free thiol groups involved in molecular unfolding of β-lactoglobulin (β-lg) can be reduced from 10 to 20 %, when a CUT of 10 s is combined with an electric field of 12 V cm⁻¹. Kinetic and multivariate analysis evidenced that the presence of an electric field during heating contributes to a change in the amplitude of aggregation, as well as in the shape of the produced aggregates. TEM discloses the appearance of small fibrillar aggregates upon the influence of OH, which have recognized potential in the functionalization of food protein networks. This study demonstrated that OH technology can be used to tailor denaturation and aggregation behavior of whey proteins due to the presence of a constant electric field together with the ability to provide a very fast heating, thus overcoming heat transfer limitations that naturally occur during conventional thermal treatments.